Kemampuan Penalaran Matematis dalam Pembelajaran Flipped Classroom Bernuansa Etnomatematika Berbantuan Edpuzzle - Nurul Alfiyah Alsalamah; Zaenuri Mastur; Isnarto Isnarto (Universitas Muria Kudus, 2022)
The purpose of this study is determine the effectiveness of students' mathematical reasoning abilities in edpuzzle-assisted ethnomathematical flipped classroom learning. The research method used for this research is a mixed method using a sequential explanatory design. The population in this study were students of class X SMA N 1 Tegal, while the sample was class X MIPA SMA N 1 Tegal. Class X MIPA 4 as the control class and class X MIPA 4 as the experimental class. The results of the study indicate that data collection is carried out by the methods of documentation, observation, questionnaires, and tests. Data analysis used one sample t test, proportion test, and independent sample t test. The results showed that 1) the average mathematical reasoning ability in the ethnomathematical-assisted flipped classroom learning with the help of edpuzzle was 79.09 so that it exceeded the actual completeness limit criteria, 2) 75% of the students in the ethnomathematical-assisted flipped classroom learning completed classically, 3) the average mathematical reasoning ability of students in the ethnomathematical nuanced flipped classroom with the help of edpuzzle is better than the average mathematical reasoning ability in problem based learning, 4) the proportion of classical completeness in the mathematical reasoning ability in the ethnomathematical-assisted flipped classroom with the help of edpuzzle is higher than classical mastery of mathematical reasoning abilities in problem based learning